Mobile Content Management System (mCMS) - PAVANA H (2005)
INTERNAL GUIDE : Loganayagi B . EXTERNAL GUIDE : Srinivasan N USN No : 1MJ04SCS10 CARRIED OUT AT : WDC Solutions (P) Ltd Bangalore ACC NO : PC27
Keywords: M.Tech Computer Science